ROLE OF AYURVEDIC DRUGS IN TREATING GERIATRIC DISORDERS AND IN IMPROVING THE QUALITY OF LIFE - A DEMONSTRATIVE PROJECT - K Bharathi; Swamy, R.K. (International Journal of Ayurveda and Pharma Research, 2016)
Present study is a demonstrative trial taken up with the aim of establishing the safety and efficacy of compound Ayurvedic drugs in geriatric people, who are institutionalised at old age home. Patients recruited under this study were suffering with minor to moderate ailments and given disease specific Ayurvedic medicines along with them one Rasayana drug like Ashvagandha/ Triphala/ Yashtimadhu/ Amalaki. Mini mental status examination (MMSE) and Hamilton Anxiety Rating Scale (HARS) tests were applied initially and after completion of six months to evaluate the efficacy of Ayurvedic drugs in treating the Geriatric problems and enhancing the quality of life on total 30 subjects recruited for this study. All the patients were undergone blood tests before and after treatment for their kidney and liver function tests. On analysis of MMSE, it is found that total 16 (53.34) cases were showed improvement; in the HARS – Psychic level, majority of cases showed improvement in all the parameters viz., anxiety, tension, fear, insomnia, intellectual and depression; similarly in the HARS-somatic level, showed improvement in all the parameters - General Somatic (muscular), General Somatic (sensory), cardio-vascular, respiratory, gastro-intestinal, genito-urinary and autonomic system symptoms. Blood markers of liver and kidney function were within normal limits in all patients before and after treatment. This indicates that the used Ayurvedic drugs are safe even in the geriatric people.